Damage mechanical properties of sandstone under combined action of freeze-thaw and load - Yongjun SONG; Jinghui CAO (Meitan kexue jishu)
Engineering rock mass in cold regions is subjected to the combined action of freeze-thaw and load for a long time, which causes deterioration in the mechanical properties of the rock mass. It will lead to all types of geological hazards and engineering accidents easily. In order to realistically reproduce the mechanical response characteristics of engineering rocks in cold regions during repeated freezing and thawing processes, the rocks were frozen and thawed under loaded (0, 15%σc, 30%σc, 40%σc，σc is the average peak strength of this batch of rock samples) state. And then the mechanical characterisation was carried out on this basis. The results indicate that: The quality loss rate of sandstone increases exponentially with the increase of freeze-thaw cycles, and the higher the loading level, the greater the quality loss rate, with a maximum quality loss of 0.37%. Moreover, the two end faces of sandstone is effected by the friction during the freeze-thaw with load test for a long-term. So, they are prone to rock matrix detachment after being disturbed. As the number of freeze-thaw cycles increases, the porosity of the rock sample increases in a power function, while the longitudinal wave velocity decreases in an exponential function. Rock samples at 15%σc undergoed freeze-thaw cycles, the porosity increases the slowest and the longitudinal wave velocity decreases the slowest. After 15 freeze-thaw cycles, the porosity increases by 6.00% and the longitudinal wave velocity decays by 7.91%. The peak strength and elastic modulus of rock samples are negatively correlated with the number of freeze-thaw cycles. The load level on sandstone during freeze-thaw process has a significant impact on its mechanical properties. In the early stage of freeze-thaw, sandstones under load had a stronger ability to resist freeze-thaw action. While under long-term freeze-thaw cycles, they had a weaker ability to resist freeze-thaw effects with the higher loading level of sandstones. The peak strain of sandstone is positively correlated with the number of freeze-thaw cycles. The peak strain of sandstone is effected by the load on the freeze-thaw process. The peak strain under uniaxial compression of loaded freeze-thaw rock samples is smaller than that of unloaded freeze-thaw rock samples. A segmented damage constitutive model considering the load freeze-thaw and mechanical loading factors is established through the basic principles of damage mechanics. The model has a fine degree of matching with experimental data. It can be well applied to describe the damage and failure process of loaded freeze-thaw rocks under loading.